Practical Cooperation between UNWTO and Uzbekistan: A Sustainable Tourism Perspective: Kerjasama Praktis antara UNWTO dan Uzbekistan: Perspektif Pariwisata Berkelanjutan - Shermahmatovich, Botir Rakhmatullaev (Universitas Muhammadiyah Sidoarjo, 2025)
Despite the collaboration of Uzbekistan with UNWTO on improving sustainable tourism, which is yet limited, no research has ever addressed the micro level impact of these efforts on hospitality training and service quality. To address this gap, this paper presents a mixed method study for the Samarkand Regency Amir Temur Hotel that includes quantitative surveying 50 employees and qualitative interviewing key management. Using PESTEL and SWOT analyses, the study reveals that while UNWTO led training enhanced staff motivation and customer satisfaction, inconsistency and high turnover hampers progress. CSR focused training programs were structured and helped improve employee engagement and retention, adding a slant on sustainability to hospitality practice. The findings indicate that the tourism sector in Uzbekistan should remain in cooperation with UNWTO and cultivate strategic HR practices to position its tourism sector as sustainable leader. Highlights: UNWTO collaboration improves training, motivation, and satisfaction. High turnover and inconsistency hinder progress. Strategic HR practices vital for sustainable tourism leadership. Key words: Sustainable tourism, UNWTO collaboration, hospitality training, employee engagement, customer satisfaction, Uzbekistan tourism, CSR, workforce development, service quality, PESTEL analysis, SWOT analysis.